Factors affecting internet and broadband penetration in South African ordinary schools - Mooketsi, Tsholofelo Rebecca (My University, 2016)
This study is about investigating the supply-side factors affecting broadband connectivity in South African ordinary schools so as to determine the challenges of providing broadband in these schools. It focuses on understanding why only 25% of these schools (RIA, 2012) have broadband connectivity whereas South Africa has resources that include; policies, legislations and regulations; available infrastructure and funding, which are aimed at advancing the Internet connectivity in schools. In this regard, this study assesses the effectiveness of the existing policies and regulations, particularly in terms of implementation, to determine where the blockages are. It also identifies the areas that require intervention. The study also examines the challenges in the provision of the existing broadband infrastructure to these schools and the effectiveness of the current funding mechanisms. The main aim of the study is to identify and analyse the supply-side blockages in the rollout of broadband connectivity in schools and then make recommendations on how to address these barriers so as to improve broadband penetration in ordinary schools. The study is premised on the notion that broadband is an educational resource that can be used to improve the delivery of education, to widen access to online educational resources and to improve the teaching and learning processes, thereby contributing positively to the quality of